The wife of Jesus ancient texts and modern scandals - Le Donne, Anthony 1975- (Oneworld, 2013)
Approaching the subject of Jesus' marital status from a fresh, historical perspective and without appealing to sensationalist stories or dismissing Jesus' sexuality on theological grounds, Le Donne places Jesus firmly within his sociocultural context. By investigating gender and marriage norms -- as well as a number of social outliers who defied them -- he provocatively argues that Jesus might have been married before he was thirty years of age. Le Donne then points to several indicators that suggest that Jesus was a sexual non-conformist and probably was single during his public career. It is a quest that illuminates the humanity of Jesus, while also revealing important connections between ancient sexuality and modern spirituality